Changes in LDL Oxidative Status and Oxidative and Inflammatory Gene Expression after Red Wine Intake in Healthy People: A Randomized Trial - Laura Di Renzo; Luigi Tonino Marsella; Alberto Carraro; Roberto Valente; Paola Gualtieri; Santo Gratteri; Diego Tomasi; Federica Gaiotti; Antonino De Lorenzo (Mediators of Inflammation)
Postprandial oxidative stress is characterized by an increased susceptibility of the organism towards oxidative damage after consumption of a meal rich in lipids and/or carbohydrates. Micronutrients modulate immune system and exert a protective action by reducing low density lipoproteins (LDL) oxidation via induction of antioxidant enzymes. We evaluated the gene expression of oxidative stress (HOSp), inflammasome (HIp), and human drug metabolism pathways (HDM) and ox-LDL level at baseline and after the intake of red wine naturally enriched with resveratrol (NPVRW), in association with or without a McDonald’s meal (McDM). The ox-LDL levels significantly increase comparing baseline (B) versus McDM and decreased comparing McDM versus McDM + NPVRW (P≤0.05). Percentages of significant genes expressed after each nutritional intervention were the following: (1) B versus McDM, 2.88% HOSp, 2.40% of HIp, and 3.37% of HDMp; (2) B versus McDM + NPVRW, 1.44% of HOSp, 4.81% of HIp, and 0.96% of HDMp; (3) McDM versus McDM + NPVRW, 2.40% of HOSp, 2.40% of HIp, and 5.77% of HDMp; (4) B versus NPVRW, 4.80% HOSp, 3.85% HIp, and 3.85% HDMp. NPVRW intake reduced postprandial ox-LDL and the expression of inflammation and oxidative stress related genes. Chronic studies on larger population are necessary before definitive conclusions.